Internet-Based Telerehabilitation Versus in-Person Therapeutic Exercises in Young Adult Females With Chronic Neck Pain and Forward Head Posture: Randomized Controlled Trial - Patcharin Nilmart; Arrada Sichuai; Asree Chedang; Chanikarn Goontharo; Nollapan Janjamsai (JMIR Rehabilitation and Assistive Technologies)
Abstract BackgroundNeck pain is a common musculoskeletal disorder, often linked to forward head posture (FHP). Studies have shown that exercise interventions can improve pain, craniovertebral angle (CVA), range of motion, and function in individuals with FHP. While telerehabilitation exercise has proven effective for other musculoskeletal conditions, its effectiveness in addressing neck pain and FHP is still being investigated. ObjectiveThis study aimed to evaluate and compare the effectiveness of an internet-based telerehabilitation therapeutic exercise program with an in-person supervised program in improving clinical outcomes among young adult females with chronic nonspecific neck pain and FHP. The study hypothesized that there would be no significant differences in outcomes between the 2 groups. MethodsA randomized controlled trial was conducted with 50 participants experiencing chronic neck pain and FHP, recruited through public announcement and voluntary sign-up. Participants were randomly assigned to either a telerehabilitation group or an in-person supervision group. Both groups completed the same 6-week, physiotherapist-supervised therapeutic exercise program, delivered via Zoom (Zoom Video Communications) or in the physiotherapy department laboratory, respectively. Outcome assessments were conducted face-to-face by blinded assessors at baseline, after 4 and 6 weeks of intervention, and at a 2-week follow-up. Outcome measures included pain intensity (assessed using the Visual Analog Scale [VAS]), CVA, neck disability (assessed using the Neck Disability Index [NDI]), and cervical range of motion (CROM). Adherence was monitored using attendance logs. ResultsOf the 50 participants, 48 completed the intervention with 1 dropout from each group. Adherence among completers was 100 percent in both groups. All 50 participants were included in the analysis using the intention-to-treat principle. No differences in effectiveness were found between the telerehabilitation and in-person groups, as no significant interaction effect between group and time was observed across all outcome measures including VAS, CVA, NDI, and CROM (PPPP ConclusionsBoth telerehabilitation and in-person supervision were similarly effective in improving pain, posture, neck disability, and CROM in young adult females with chronic neck pain and FHP. These findings suggest that telerehabilitation may be a feasible and accessible alternative to conventional in-person therapeutic exercise programs for managing chronic neck pain with FHP.